2010
DOI: 10.1128/aac.00580-10
|View full text |Cite
|
Sign up to set email alerts
|

LmrS Is a Multidrug Efflux Pump of the Major Facilitator Superfamily from Staphylococcus aureus

Abstract: A multidrug efflux pump designated LmrS (lincomycin resistance protein of Staphylococcus aureus), belonging to the major facilitator superfamily (MFS) of transporters, was cloned, and the role of LmrS in antimicrobial efflux was evaluated. The highest relative increase in MIC, 16-fold, was observed for linezolid and tetraphenylphosphonium chloride (TPCL), followed by an 8-fold increase for sodium dodecyl sulfate (SDS), trimethoprim, and chloramphenicol. LmrS has 14 predicted membrane-spanning domains and is ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
114
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(117 citation statements)
references
References 47 publications
3
114
0
Order By: Relevance
“…The only clear nonribosomal linezolid resistance mechanism reported is related to mutations causing increased expression of ABC transporter genes in Streptococcus pneumoniae (3,19). It has also been shown that Staphylococcus aureus possesses a gene for a majorfacilitator-superfamily-type multidrug efflux pump named LmrS that is capable of extruding linezolid (21).…”
Section: Linezolidmentioning
confidence: 99%
“…The only clear nonribosomal linezolid resistance mechanism reported is related to mutations causing increased expression of ABC transporter genes in Streptococcus pneumoniae (3,19). It has also been shown that Staphylococcus aureus possesses a gene for a majorfacilitator-superfamily-type multidrug efflux pump named LmrS that is capable of extruding linezolid (21).…”
Section: Linezolidmentioning
confidence: 99%
“…In fact, alterations in these ribosomal proteins are currently often observed among staphylococcal isolates, especially among coagulase-negative staphylococci, demonstrating a shift in the epidemiology of linezolid-nonsusceptible isolates and associated resistance mechanisms (2). Efflux-pump mechanisms have also been implicated as a linezolid resistance mechanism (5), and a plasmid-mediated gene (transferable) was recently described (6).…”
mentioning
confidence: 99%
“…For example, the aerobic MIC of php was found to vary between 4 g mL −1 (S. epidermidis) and 500 g mL −1 (S. aureus ATCC 29213) [52], and in another study the death percentage of S. aureus ATCC 26923 in 20 g php mL −1 was 32% [114]. It is conceivable that, as discussed above for S. aureus, pyp exerted its intrinsic effect on the manure microbiota through inhibition of a MDR efflux pump, such as LmrS, MdeA, and possibly NorA, as these and their homologues occur in B. subtilis, a major component of MicroSource S, and are widespread among other low mol percentage guanine-cytosine Gram-positive (phylum Firmicutes) bacteria [27,81,97,100,[115][116][117], the predominant culturable anaerobic microorganisms from swine manure [73,118,119].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, efflux-mediated antimicrobial resistance is controlled by the metabolic condition of bacteria and can be altered by a switch from an aerobic to an anaerobic metabolism through the influence of metabolically integrated global regulators, different endogenous cellular metabolites, such as ROS from aerobic respiration or anaerobic fermentation end products which often times are the natural pump substrates, and an altered transmembrane electrochemical proton gradient as energy source for secondary active transporters [27,28,32,80]. Hence, it can be presumed that the higher level of induced resistance in S. aureus under anaerobic conditions was contingent on a switch from glycolysis, the pentose phosphate pathway and ROS generating tricarboxylic acid cycle under aerobiosis to anaerobic glucose fermentation and ATPase-mediated proton efflux, generating a greater motive force for erythromycin-proton antiporters [28,80,94], such as LmrS, MdeA, Mef(A), and conceivably NorA [27,32,[95][96][97].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation